2021
DOI: 10.3390/polym13172841
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Computational Methods for the Development of Molecularly Imprinted Polymers

Abstract: Recent years have witnessed a dramatic increase in the use of theoretical and computational approaches in the study and development of molecular imprinting systems. These tools are being used to either improve understanding of the mechanisms underlying the function of molecular imprinting systems or for the design of new systems. Here, we present an overview of the literature describing the application of theoretical and computational techniques to the different stages of the molecular imprinting process (pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 661 publications
(507 reference statements)
0
27
0
Order By: Relevance
“…Appropriate simulations and computations have led to new methods for describing, predicting, and analyzing the complexity of molecular imprinting process without repeated laboratory experiments, an endeavor that saves time, energy, and the disposal of chemicals [ 42 , 43 , 44 , 45 ]. Researchers have demonstrated that computational studies based on molecular dynamics (MD) simulations can provide a realistic description of functional monomer-template interactions and, at the same time, explore the effects of different monomer ratios in the polymerization mixture [ 42 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate simulations and computations have led to new methods for describing, predicting, and analyzing the complexity of molecular imprinting process without repeated laboratory experiments, an endeavor that saves time, energy, and the disposal of chemicals [ 42 , 43 , 44 , 45 ]. Researchers have demonstrated that computational studies based on molecular dynamics (MD) simulations can provide a realistic description of functional monomer-template interactions and, at the same time, explore the effects of different monomer ratios in the polymerization mixture [ 42 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the introduction of computational techniques into the field, researchers had explored the use of various theoretical treatments [27][28][29], combinatorial polymer synthesis approaches [30,31] and various spectroscopy-based studies [32][33][34][35]. It was, however, with the introduction of computational chemistry into the molecular imprinting field, particularly when used together with experimental studies, that significant interest in rational MIP design and understanding of molecular level details of MIP systems began to evolve, as can be followed through a series of reviews of the area over the period [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The increased use of computational chemistry for better understanding the various aspects of the molecular imprinting process and for the design of novel MIPs has been driven by the establishment of more powerful computers, better theoretical descriptors, and purpose-oriented software.…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of computational chemistry for better understanding the various aspects of the molecular imprinting process and for the design of novel MIPs has been driven by the establishment of more powerful computers, better theoretical descriptors, and purpose-oriented software. Collectively, these developments have, and continue to, pave the way for more precise and efficient modeling of molecular level structure and interactions in molecular imprinting systems, as reflected in the growing numbers of publications deploying computational chemistry [48]. Three broad classes of computational methods have been applied to the study and development of aspects of the molecular imprinting process and for understanding specific MIP systems: quantum mechanicsbased studies, statistical studies (most notably multivariate analysis) and molecular mechanics-based molecular dynamics studies [48].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations